Pregnancy after 35 years of age - Naworska, Beata; Drosdzol-Cop, Agnieszka; Kobiałka, Agnieszka; Skrzypulec-Plinta, Violetta (Menopause Review/Przegląd Menopauzalny, 2012)
The course of pregnancy among women aged 35 years and over is considerably affected by both the state of health before gravidity and the obstetric and gynaecological factors in the past. Analysis of health behaviour among women has demonstrated that there is a necessity of steady education of female patients about early and systematic obstetric care during pregnancy, attending the school of birth, folic acid supplementation as well as smoking cessation during pregnancy. Complications of the course of pregnancy and perinatal complications concern more frequently women aged 35 years and over, and delivery in this age group more frequently resulted in a caesarean section, mainly owing to elective indications.